The diverse expression of the WT1 gene in patients with acquired bone marrow failure syndromes. Issue 4 (3rd April 2018) - You, Yahong; Huo, Jiali; Lu, Shihong; Shao, Yingqi; Ge, Meili; Shi, Jun; Li, Xingxin; Huang, Jinbo; Huang, Zhendong; Zhang, Jing; Wang, Min; Nie, Neng; et al.
Abstract: Acquired bone marrow failure syndromes (aBMFS) encompass a wide range of diseases. A study to investigate WT1 expression in BM was conducted in 387 patients with aBMFS in China. The WT1 level in patients with aplastic anemia (AA) was significantly lower than that in patients with paroxysmal nocturnal hemoglobinuria (PNH, p  = .023) and myelodysplastic syndrome (MDS, p  < .001). In addition, the WT1 level in patients with MDS significantly increased as the disease progressed to an advanced stage. Patients with hypoplastic MDS had a differentiated expression level of WT1 compared with that of NSAA ( p  < .001). Furthermore, post-treatment patients of AA with partial response (PR) or complete response (CR) status had relatively higher WT1 levels than those with naive AA ( p  = .017, p  = .003, respectively). Thus, the WT1 expression level could be a useful genetic marker for routine clinical work in aBMFS.